Assessment of Mental Health Implications of Technology-Mediated Instructions among University Students in the Post Covid-19 Era - Adebayo, David Obafemi (International Journal of Educational Management, 2021)
Technology use in the classroom has significantly changed students’ learning and classroom activities particularly in universities nowadays, more importantly, as Covid-19 pandemic ravages the world. It is however not without its own challenges especially mental health implications for learners. This study examined mental health implications of technology mediated instructions among university students. It is a quantitative study and it adopted survey design. Three research questions guided the study and four null hypotheses were tested. A total of 300 university students randomly selected from various faculties in the university participated in the study. A self-designed questionnaire entitled “Assessment of Mental Health Implications of Technology Mediated Instruction (AMHITMIQ)” was employed to collect data for the study. The instrument possessed a reliability coefficient of 0.85 having been subjected to a Test-re-test method of reliability. Mean, Percentage, and Analysis of Variance (ANOVA) statistical tools were used to analyse the data collected. Hypotheses were tested at 0.05 alpha levels of significance. Results revealed that poor internet connections often experienced, negative effect of technological devices on one’s sight, topped the list of indices of mental health implications of technology mediated instructions according to the students sampled. Results revealed that there was significant difference in students’ views on mental health implications of technology mediated instructions based on age; whereas, for levels of study, exposure to technology and combined family’s monthly incomes, there were no significant differences. The study recommended among others that constant checks in the use of technology driven instructions by lecturers in order to accommodate various needs of learners in the classroom and to also ensure they are carried along in the process.